INFORM: An Information System for Agricultural Research Management - Vernon, Richard (International Service for National Agricultural Research, 1995)
National agricultural research systems were comparatively well funded in the 1960s and early 1970s. In the 1980s and early 1990s, however, they have faced a more difficult economic climate. With the limited resources now available it has become increasingly important to raise the efficiency of agricultural research in order to maximize the output of enhanced technology to farmers. This challenge is the responsibility of research managers. To meet it they need good information about the research systems they manage: information about inputs to research (people, finance, and physical resources), the research program (experiments), and finally, research outputs (improved technologies and reports on experiments and impact). Such information should be available in aggregate form so that managers are not overburdened by detail. It should be timely, reasonably accurate, and available in various forms to serve particular management issues. A tool to provide managers with this information is called a management information system. ISNAR, in collaboration with a number of countries' national agricultural research systems (NARS), has developed such a system, called INFORM (Information for Agricultural Research Managers).